Penerapan Teknologi Blockchain dalam Meningkatkan Keamanan Sistem Identifikasi Pengguna - Afdilah, Sonia; Agustina, Nova Sari; Hani, Ilfa; Gunawan, Gunawan (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2024)
In today's digital era, the security of the user identification system must be considered, therefore the use of blockchain technology can be utilized in such a way. Blockchain is a dynamic and interactive computer program to support solving problems in identifying users. Apart from that, blockchain technology can be used to secure data which is now very vulnerable to viruses in computers or networks. Blockchain technology provides a solution by providing a strong and reliable information security system. Blockchain technology can be used to ensure the integrity and validity of stored data. This can be done by storing data in blocks that are connected to each other and using encryption to maintain privacy. In addition, the decentralized system in blockchain technology makes it difficult to change or delete by irresponsible parties. Blockchain technology is very suitable for increasing the security of user identification systems, in this research the author found other research related to blockchain technology which is useful for data security, therefore the author invites readers to use blockchain technology for the security of user identification systems and data security.